Structural and electrical properties of novel Mg0.9+0.5yZn0.4AlyZr1.6−y(PO4)3 ceramic electrolytes synthesized via nitrate sol–gel method - Anuar, N.K.; Mohamed, Nor Sabirin (Springer Verlag, 2016)
Magnesium-based Nasicon-type compounds with formula Mg0.9+0.5yZn0.4AlyZr1.6−y(PO4)3, (0.0 ≤ y ≤ 0.4) were prepared by the nitrate sol–gel method and characterized by X-ray diffraction, particle size analyser, scanning electron microscopy, energy-dispersive X-ray spectroscopy and impedance spectroscopy. The substitution of Zr4+ by a smaller Zn2+ and Al3+ cations reduced the unit cell dimensions of the parent compound’s structure to form a more stable framework and enhanced its conductivity by about three orders of magnitude. X-ray diffraction spectra clearly indicated the formation of single-phase compounds without any impurity. The compounds belong to the monoclinic structure with P21/n space group. The substitution of Al3+ and Zn2+ in zirconium sites did not affect the formation of the single phase, and this probably due to the concentration of both Al3+ and Zn2+ was too low to induce structural changes. The AC conductivity analysis demonstrated that the increase in conductivity was mainly due to an increase in the number of mobile ions. The Mg1.05Zn0.4Al0.3Zr1.3(PO4)3 exhibited the highest conductivity in the order of 10−4 S cm−1.